2018
DOI: 10.32598/rj.19.2.150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family-Centered Nature Therapy on Children With Autism Spectrum Disorder

Abstract: Objective The treatment of autism, a long-term developmental neurological disorder, is controversial. Because of the increasing trend and the lack of a known cause in this area, the treatment is complicated; obscure development of the disorder is a fundamental issue for the parents of these children. Due to the nature of the disorder and involvement of long durations of treatment, various therapeutic methods are used. In addition to the present treatments, a cost-effective and effective treatment is nature the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The current study also demonstrated that familycentered counseling led to an improvement in respiratory indices, including FEV1 in children with asthma three FEV1 is the amount of air exhaled during the first second of the FVC maneuver, and its amount decreases in lung diseases, including asthma (29). Smoking cessation leads to an improvement in pulmonary function and an increase in the FEV1 index (28).…”
Section: Discussionmentioning
confidence: 54%
“…The current study also demonstrated that familycentered counseling led to an improvement in respiratory indices, including FEV1 in children with asthma three FEV1 is the amount of air exhaled during the first second of the FVC maneuver, and its amount decreases in lung diseases, including asthma (29). Smoking cessation leads to an improvement in pulmonary function and an increase in the FEV1 index (28).…”
Section: Discussionmentioning
confidence: 54%
“…There were significant shortcomings in access to services, including referral problems for essential services in Jeddah, Saudi Arabia. • Challenges related to the high costs of services and the lack of a systematic support system: High cost of providing services [15], insufficient insurance coverage [13], lack of government support [26], and concerns about costs [21];…”
Section: Dern and Sappokmentioning
confidence: 99%
“…• Challenges related to poor knowledge and attitude: Lack of knowledge of the signs and symptoms of ASD [26], lack of information of parents about how to access the required services [15], and lack of knowledge about ASD [22];…”
Section: Dern and Sappokmentioning
confidence: 99%
See 2 more Smart Citations